2015
DOI: 10.1016/j.redox.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Redox implications in adipose tissue (dys)function—A new look at old acquaintances

Abstract: Obesity is an energy balance disorder associated with dyslipidemia, insulin resistance and diabetes type 2, also summarized with the term metabolic syndrome or syndrome X. Increasing evidence points to “adipocyte dysfunction”, rather than fat mass accretion per se, as the key pathophysiological factor for metabolic complications in obesity. The dysfunctional fat tissue in obesity characterizes a failure to safely store metabolic substrates into existing hypertrophied adipocytes and/or into new preadipocytes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 195 publications
(256 reference statements)
0
73
0
1
Order By: Relevance
“…It is consequently plausible that olive‐oil‐based HFDs facilitate the availability and balance of NAD + for local demands during expansion of WAT in niacin‐treated mice. In fact, NAD + also acts as cofactor in metabolic redox reactions that are key to mitochondrial bioenergetics and to accommodate energy surplus safely in adipocytes . For the first time, our data are suggestive of a regulatory role of dietary fatty acids in combination with niacin on adipose NAD + during HFD‐induced obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 58%
“…It is consequently plausible that olive‐oil‐based HFDs facilitate the availability and balance of NAD + for local demands during expansion of WAT in niacin‐treated mice. In fact, NAD + also acts as cofactor in metabolic redox reactions that are key to mitochondrial bioenergetics and to accommodate energy surplus safely in adipocytes . For the first time, our data are suggestive of a regulatory role of dietary fatty acids in combination with niacin on adipose NAD + during HFD‐induced obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, mitochondrion is both the origin and target of multiple metabolic signals whose integration maintains insulin sensitivity. Importantly, it has been suggested that mitochondrial redox signaling has a key role in white adipose tissue, regulating different processes such as adipocyte differentiation or adiponectin secretion through the modulation of redox-sensitive transcriptional factors [12], [13]. Not surprisingly, given that white adipose tissue is the greatest endocrine organ in the human body any alteration in adipocyte mitochondria could result in significant homeostatic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging paradigm is that redox imbalances in fat tissue may play a pivotal role in the onset of adipocyte dysfunction with obesity [5]. For example, oxidative stress in fat cells impaired systemic insulin sensitivity and is an early instigator of insulin resistance onset [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a major health problem that is usually associated with obesity, together with hyperglycemia and advanced glycation endproducts (AGEs) formation. The concept of redox imbalance (in fat tissues) as an instigator of adipocyte dysfunction with obesity is a recent phenomenon [5]. For example, oxidative stress impaired systemic insulin sensitivity and played a causative role in the development of insulin resistance in adipose tissues [4,6].…”
Section: Introductionmentioning
confidence: 99%